SIMBOL YIN YANG SEBAGAI KONSEP PENCIPTAAN MEJA TERAS - Sayf Iqbal Mahatir Ahmad (SULUH: Jurnal Seni Desain Budaya, 2020)
Yin and Yang describe the properties that are interconnected, opposite, and complementary to each other. Yin is more to the black side and yang is the white side of the opposite color side. The tiny black and white dots that are on Yin and Yang represent the sides that complement each other. The table is a piece of furniture that we often encounter inevery home, be it a dining table, a guest table or a terrace table, because of its function which has many roles as a support for human activity, we find lots of unique and creative table models and shapes. Based on this, the problems raised in this case are (1)How to make a terrace table design, which is able to support human activities, (2) How to apply the Yin Yang form to modern-style patio table products. (3) How to make an innovative patio table.